Reengineering of LED AII 451 Cover Using QFD to Enhance Manufacturing Efficiency and Product Safety - Juliansyah Juliansyah; Hery Irwan (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2026)
Production efficiency and manufacturability are critical factors for industrial competitiveness, particularly for components such as protective covers for the LED AII 451 lighting unit. The existing cover design relies on conventional machining and consists of five separately manufactured parts, resulting in high assembly time and elevated production cost. This study applies Quality Function Deployment (QFD) to reengineer the LED AII 451 cover in order to improve manufacturing efficiency, simplify assembly, and enhance product safety. Customer needs were collected from 25 respondents (20 production operators and 5 maintenance technicians) through interviews, questionnaires, and direct technical observation, and were translated into technical parameters using the House of Quality. The analysis identified six prioritized technical improvements: tailoring the manufacturing process to product dimensions, adopting a lightweight plastic material (Delrin/PVC), reducing the total component count, using screw-based assembly, incorporating chamfered edges, and ensuring material strength and durability. The redesigned cover reduced the number of components from five to three (40% reduction), decreased average assembly time from 12 to 9 minutes (25% reduction), and lowered relative production cost from 100% to 85% (15% reduction), while also improving ergonomics and operator safety. These results demonstrate that QFD provides a structured, quantitatively validated approach for translating customer requirements into manufacturable design improvements for industrial lighting protection components.